2022
DOI: 10.1111/jfpp.16819
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement of freeze‐dried carrots as affected by sugar‐osmotic and hot‐air pre‐treatments

Abstract: To improve the visual-sensory and nutritional quality of freeze-dried carrots (FDC), the effects of sugar-osmotic dehydration (SO, 40°Brix, 3 h) and hot-air pre-drying (HAPD, 80°C, 10 min) on the FDC quality were investigated. Overall, SO&HAPD significantly improved the redness (8.26%-11.67%), yellowness (1.24%-5.82%) and ABTS radical scavenging activity (1.40%-16.00%) of FDC. FDC pre-treated by sucrose showed the highest a* value (33.31), which was related to the β-carotene content. The influence order of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…They confirmed that the combined microwave FD dynamic microwave logic control process can improve the drying efficiency by up to 60 % compared to the original FD process. The impacts of osmotic dehydration (glucose, sucrose, honey, and mannitol solutions, 40°Brix, 3 h) and hot-air predrying (oven, 80 °C, air velocity 2.0 m s -1 , 10 min) on the freeze-dried carrots quality were examined by Lyu et al [52]. They confirmed that the pretreatment with osmotic solutions and hot-air significantly improved the redness index (8.3-11.7 %), yellowness index (1.24-5.82 %), and 2,2-azinobis-(3-ethylbenzothiazoline-6sulphonate) (ABTS) radical scavenging activity (1.4-16.0 %) of freeze-dried samples.…”
Section: Carrotsmentioning
confidence: 99%
“…They confirmed that the combined microwave FD dynamic microwave logic control process can improve the drying efficiency by up to 60 % compared to the original FD process. The impacts of osmotic dehydration (glucose, sucrose, honey, and mannitol solutions, 40°Brix, 3 h) and hot-air predrying (oven, 80 °C, air velocity 2.0 m s -1 , 10 min) on the freeze-dried carrots quality were examined by Lyu et al [52]. They confirmed that the pretreatment with osmotic solutions and hot-air significantly improved the redness index (8.3-11.7 %), yellowness index (1.24-5.82 %), and 2,2-azinobis-(3-ethylbenzothiazoline-6sulphonate) (ABTS) radical scavenging activity (1.4-16.0 %) of freeze-dried samples.…”
Section: Carrotsmentioning
confidence: 99%